2012
DOI: 10.1556/mental.13.2012.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among aerobic exercise, psychological well-being, self-esteem, and body awareness in women – An empirical study

Abstract: Elméleti háttér: Számos vizsgálat kimutatta a rendszeres sport pozitív hatásait: jobb emocionális és pszichés állapot, az önértékelés növekedése a fizikai hatékonyságon keresztül, a testrõl alkotott kép és testi tudatosság javulása. Cél: A tanulmány célja a rendszeres aerobikozás pszichológiai jólléttel, önértékeléssel, valamint testi tudatossággal való feltéte-lezett pozitív együttjárásának vizsgálata volt. Ismereteink szerint a mai napig nem jelent meg az önértékelés és a testi tudatosság kapcsolatát vizsgál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Perceived physical competence is associated with global self-esteem (Sági et al, 2012;. It would be logical to assume that those with better proprioceptive accuracy can execute their movements more efficiently due to more accurate processing of feedback , and thus have higher physical competence.…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived physical competence is associated with global self-esteem (Sági et al, 2012;. It would be logical to assume that those with better proprioceptive accuracy can execute their movements more efficiently due to more accurate processing of feedback , and thus have higher physical competence.…”
Section: Self-esteemmentioning
confidence: 99%
“…The relationship between physical competence and proprioceptive accuracy has been shown empirically: elite athletes with better proprioceptive ability generally achieve better results . In addition, it is also known that regular physical activity is positively associated with both self-esteem and proprioceptive accuracy (Ribeiro & Oliveira, 2010;Sági et al, 2012). Of course, many factors other than proprioceptive ability can contribute to physical competence, and perceived physical competence does not necessarily correspond to actual physical competence, this relationship might be more complex.…”
Section: Self-esteemmentioning
confidence: 99%
“…The use of questionnaires to measure well-being and IS might provide a more direct answer to the question of adaptivity. Cross-sectional empirical studies consistently revealed weak to moderate (r = 0.09 -0.42, p < 0.05) positive association between IS (as assessed by the Body Awareness Questionnaire, the Multidimensional Assessment of Interoceptive Awareness scale and the Somatic Absorption Scale) and various indicators of psychological and subjective well-being (as assessed by the Satisfaction with Life Scale, the Scales of Psychological Well-Being and the short Well-Being Index of WHO) (Brani, Hefferon, Lomas, Ivtzan, & Painter, 2014;Hanley, Mehling, & Garland, 2017;Köteles et al, 2012;Sági, Szekeres, & Köteles, 2012;Tihanyi, Böőr, Emanuelsen, & Köteles, 2016). For example, well-being as assessed by the Scales of Psychological Well-Being (Ryff, 1989) showed weak to medium associations with 7 of the 8 sub-scales of the Multidimensional Assessment of Interoceptive Awareness scale (Hanley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%